Anaerobic and aerobic skin bacteria before and after skin-disinfection with chlorhexidine: an experimental study in volunteers. - Nielsen, M L (1975)
The amount, composition, and localization of anaerobic and aerobic bacteria in the normal skin before and after disinfection were the subject of a volunteer study. The superficial bacterial flora were sampled by velvet pad imprints, and the deep flora were determined from whole skin biopsies. Only one anaerobic species, Propionebacterium acnes, was encountered even though other and more strict anaerobic bacteria could have been grown with the anaerobic technique employed. Staphylococcus albus dominated among the aerobic superficial bacteria, while diphtheroids, Micrococcus spp., and lactobacilli occurred sporadically. The deep aerobic bacteria were present in a significantly greater amount than the anaerobic. A two-step cleansing/disinfection procedure was evaluated in vivo in volunteers as well as in surgical patients, and aqueous cetrimide/chlorhexidine (Savlon) followed by chlorhexidine in alcohol (Hibitane) almost eradicated both the superficial and deep anaerobic and aerobic skin flora.